Decidual Control of Trophoblast Invasion. (12th January 2016) - Sharma, Shipra; Godbole, Geeta; Modi, Deepak
Abstract : At the time of implantation, the trophoblast cells of the embryo adhere and then invade into the maternal endometrium and eventually establish placentation. The endometrium at the same time undergoes decidualization, which is essential for successful pregnancy. While the NK cells of the decidua have been implicated to play a key role in trophoblast invasion, few evidence are now available to demonstrate a pro‐invasive property of decidual stromal cells. Secretions from decidualized endometrial stromal cells promote invasion of primary trophoblasts and model cell lines by activating proteases and altering expression of adhesion‐related molecules. The decidual secretions contain high amounts of pro‐invasive factors that include IL‐1β, IL‐5, IL‐6, IL‐7, IL‐8, IL‐9, IL‐13, IL‐15, Eotaxin CCL11, IP‐10 and RANTES, and anti‐invasive factors IL‐10, IL‐12 and VEGF. It appears that these decidual factors promote invasion by regulating the protease pathways and integrin expression utilizing the STAT pathways in the trophoblast cells. At the same time the decidua also seem to secrete some anti‐invasive factors that are antagonist to the matrix metalloproteinases and/or are activators of tissue inhibitors of metalloproteinases. This might be essential to neutralize the effects of the invasion‐promoting factors and restrain overinvasion. It is tempting to propose that during the course of pregnancy, the decidua must balance the production of these pro and anti‐invasive molecules and such harmonizing production would allow a timely and regulated invasion.